Nitrofurantoin susceptibility of ESBL gram negative isolates from patients with urinary tract infection (UTI) in a rural teaching hospital of Telangana - Dr Neelima A; Dr. Kiranmai (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: Urinary tract infections (UTI) are the most common bacterial infections affecting humans throughout their lifetime. Escherichia coli are the most common pathogen in UTIs. Extended Spectrum Beta lactamase (ESBL)-producing E. coli-related UTI is an emerging problem in many parts of the world. Nitrofurantoin has been used for a long time, but the emergence of antibiotic resistance and the decline in newly developed antibiotics has increased interest in treatment of bacterial UTI with this antibiotic.Materials & methods: A descriptive analysis of culture results of urine samples was performed at Microbiology department of MediCiti Institute of Medical Sciences from October 2014 to September 2015. Clean-catch midstream morning urine specimens were collected using sterile wide mouth disposable plastic container. The specimens were inoculated on nutrient agar, blood agar, and MacConkey agar plates and incubated aerobically at 37°C for 24-48 hours. Culture plates with colony counts of ≥ 105 colony forming units (CFU) were considered positive for UTI. Antimicrobial susceptibility was performed according to CLSI guidelines.Results: A total of 2078 cases were included in the study, out of which 485(23.33%) were males and 1593 (76.66%) females. Male to female ratio was 1:3.2. Majority of the cases (67.2%) belonged to age group 20-40 years. Escherichia coli (E.coli) (60.58%) was the most common pathogen among Gram negative isolates. 153 ESBL’S (49.83%) were reported in this study. Among these 153 isolates of ESBL producer’s nitrofurantoin resistance was seen in 44 (28.75%) isolates.Conclusion: E.coli remained the predominant isolate among gram negative organisms, more commonly in females presenting to our hospital. The in vitro activity of Nitrofurantoin found in the present study suggests that this drug would provide adequate fluoroquinolones sparing alternative therapy at places where Cotrimoxazole use is no longer prudent because of high rates of resistance. This study shows that nitrofurantoin can be used even for drug resistant strains.